Avaliação dos mecanismos de ação envolvidos no efeito anti- inflamatório da LQB 118 - Lima, Éssia de Almeida (2023)
LQB 118 is a synthetic hybrid molecule belonging to the group of pterocarpanquinones, with its structure based on two groups of natural bioactive molecules, naphthoquinones and pterocarpans. The immunomodulatory role of LQB 118 has been demonstrated by our research group, however, the mechanisms of action involved are not yet fully elucidated. Therefore, the aim of this work was to evaluate the mechanisms involved in the anti-inflammatory activity of LQB 118 in vitro and in vivo. Initially, for in vitro experiments, Swiss mice received an intraperitoneal injection of thioglycolate (4%). After four days, peritoneal macrophages were cultured at concentrations of 2x105, 5x105 or 1,5x106 cells/well. The cells were treated with LQB 118 (0.1 μM, 0.5 μM, 1 μM or 5 μM) in the presence or absence of the inflammatory stimulus, zymosan (0.2 mg/mL), for 40 min or 24h. Then, supernatants were collected for the quantification of cytokines IL-10 and IL-12 via ELISA and nitric oxide through the Griess reagent. Additionally, phagocytic activity was assessed towards zymosan particles. Finally, in order to examine the mechanism of action of the molecule, cells were incubated with anti-iNOS, anti-NFκB, anti-P-NFκB, anti-P-Akt, anti-P-mTOR, CellRox Green antibodies along with fluorescent zymosan particles and analyzed through flow cytometry. Zimosan induced an increase in cytokines and nitric oxide, and treatment with LQB 118 was able to reduce the levels of IL-12 (0.1 μM by 28.7%; 0.5 μM by 31%; 1 μM by 36.8%; and 5 μM by 57.6%) and NO (5 μM by 60.2%) without interfering with IL-10 levels. In addition, LQB 118 negatively modulated the expression of total NFκB (21.7%) and phosphorylated NFκB (59.4%), decreased the phagocytic capacity of peritoneal macrophages (24.1% in plate and 64.4% by flow cytometry), ROS production (23.5%), and reduced levels of phosphorylated mTOR (20.2%). Moreover, the effect of LQB 118 was evaluated in vivo, in a zymosan-induced peritonitis model. For this, Swiss mice were treated via i.p. with LQB 118 at doses of 10 or 20 mg/kg. One hour after treatment, they were stimulated with zymosan (2 mg/mL) to induce peritoneal inflammation. After 4h, peritoneal lavage was collected and used for total and differential cell counting by light microscopy, for quantification of cytokines TNF-α, IL-1β, IL-6, and IL-10 by ELISA, and for analysis of MAP kinase p38 expression by flow cytometry. Zymosan, as expected, induced an increase in cell migration, cytokine levels, and p38 phosphorylation. Treatment with LQB 118, on the other hand, reduced the total number of cells in the peritoneal cavity, by decreasing the migration of polymorphonuclear cells. Furthermore, this molecule was able to reduce the levels of cytokines IL-1β, TNF-α, and IL-10 and negatively modulate zymosan-induced p38 phosphorylation. Treatment with LQB 118, on the other hand, was able to reduce the total number of cells in the peritoneal cavity (32.6% at a dose of 10 mg/kg or 51.1% at a dose of 20 mg/kg), by decreasing the migration of polymorphonuclear cells (56.7% for 10 mg/kg or 80.4% for 20 mg/kg). Furthermore, this molecule was capable of reducing the levels of the cytokines IL-1β (81.1% or 78.3% for doses of 10 mg/kg or 20 mg/kg, respectively), TNF-α (56.2% at a dose of 20 mg/kg), and IL-10 (71.6% at a dose of 20 mg/kg), and negatively modulating the phosphorylation of p38 induced by zimosan (51.6%).Thus, these data demonstrate the mechanisms involved in the anti- inflammatory activity of LQB 118 and contribute to the understanding of the potentialities of this substance to act in inflammation physiological processes.